P197 PET-FDG staging for lung cancer: outcome of high uptake FDG at extrathoracic sites. (2nd December 2011) - Selvaraj, S; Garbett, K; McAdam, J; Naicker, T R; Srinivasan, K S; Moudgil, H
Abstract : Background: Positron Emission Tomography (PET) scanning withF-18 2-fluoro-2-deoxy-D-Glucose (FDG) is pivotal in staging lung carcinoma where curative intent is proposed and increasingly is being evaluated in measuring response to therapy as well as in detecting recurrent disease. Staging nodal disease in the mediastinum apart, PET has also been reported to improve the non-invasive detection of unsuspected extra thoracic disease in upto 10% and may alter management in up to 40% of cases [McLoud TC, Cancer Imaging 2003]. The limited resolution of PET, however, results in subsequent investigations and to quantify this further we have reviewed our experiences. Methods: Over a 2-year period to end 2010, 236 patients were identified as investigated by PET scan after an initial discussion of all lung cancer patients at multi-disciplinary meeting (MDT). Of these, 21 (11%) had high uptake FDG with potential evidence of extra thoracic disease not previously identified. Mean (range) age for this group was 69 (54–82) years with13 male and eight female. Results: Of the 21 patients, 13 included high uptake in the bowel with two in each of breast, thyroid, and musculo-skeletal and one in stomach and parotid. 4 patients were then not investigated further; these included one where PET-FDG findings were ignored after further MDT discussion, one was too unwell to investigate and died shortly thereafter, and two who refused further investigation. Of the remainder, 12 had high uptake FDG in the bowel but all were found to be benign after subsequent investigation, and five confirmed malignant disease of which two had thyroid cancer, two-breast cancer, and one had a prior history of bowel cancer. Over this 2-year time period none of the initially PET negative cases subsequently developed radiological malignancy. Conclusion: For extra thoracic disease, our experience with PET-FDG potentially reports sensitivity and a negative predictive power of 100% with a specificity of 95% and a positive predictive value of 29%. Although among our cases 11% had the suggestion of positive extra thoracic disease, the majority (71%) were then found to be benign with a concentration particularly at bowel. Further work will probably be needed to guide future investigation of potentially false positive metabolic or inflammatory findings at this site, but uptake at the other sites, potentially a concurrent primary malignancy or metastases, cannot be ignored.